Health-Related Quality of Life with Cervical Cancer and Precancer: A Cross-Sectional Study in Yunnan Province, China - Min Zhao; Meng-Jiao Zhang; Lian-Ju He; Chun-Mei Zuo; Song-Rui Ding; Allison Rabkin Golden; Le Cai (Clinical and Experimental Obstetrics & Gynecology)
Background: Cervical cancer is the fourth most common cancer in women, with an estimated 600,000 new cases and 340,000 deaths worldwide in 2020. However, there remains limited understanding of the association between individual socioeconomic status, clinical characteristics, and health-related quality of life (HRQoL) of women with cervical precancerous lesions. This study investigates socioeconomic and clinical variations in HRQoL of women with cervical precancerous lesions and cervical cancer in Yunnan Province, China. Methods: The present study employed a cross-sectional survey design. An EuroQol Five Dimensions Five Level (EQ-5D-5L) questionnaire was used to assess HRQoL of 400 patients with cervical precancerous lesions and cervical cancer in Yunnan Province, China, from 2019 to 2020. Analysis of variance (ANOVA) and independent samples t-tests were performed to identify the independent variables associated with EQ-5D-5L utility scores and visual analogue scale (VAS) scores. Predictors of utility scores were confirmed using a Tobit regression model. Results: The mean EQ-5D-5L utility scores of cervical precancerous lesions and cervical cancer patients was 0.939 (standard deviation (SD), 0.104), and the mean VAS score was 80.84 (SD, 16.551). Patients aged 40–59 years (β = –0.037, p = 0.005), patients who were not aware of the human papillomavirus (HPV) vaccine (β = –0.032, p = 0.004), and patients who underwent radical hysterectomy (β = –0.036, p = 0.006) had significantly lower utility scores, whereas having high monthly household income (β = 0.023, p = 0.033) was significantly associated with higher EQ-5D-5L utility scores. Age (p = 0.023) was statistically significant in differences in patients’ VAS scores. Anxiety/depression was the most frequently reported issue (35.75%) among participants. Conclusions: Future cervical cancer prevention and treatment guidelines should focus on low-income women, women aged 40–59 years, and those lacking knowledge about cervical cancer prevention.